Edukasi Kesehatan Pencegahan Stunting Bagi Masyarakat - Merita Eka Rahmuniyati; Ayu Fitriani; Yelli Yani Rusyani; Rodiyah Soekardi; Heni Trisnowati; Cahyaningtyas Triwinarni; Ndari Melinda Saputri; Nurhayati Nurhayati (Humanism: Journal of Community Empowerment (HJCE), 2023)
Stunted children are very vulnerable to various kinds of diseases from childhood to adulthood. Based on the situation analysis, several problems faced by partners can be identified, namely there are still cases of stunting, possibly because there are still stunted toddlers and babies born with LBW and the level of knowledge of mothers/families/cadres/young women regarding stunting is still low. The purpose of this service is to increase public knowledge about stunting which includes its meaning, causes, effects, and prevention efforts. This Community Service activity is in the form of health education activities with counseling methods related to stunting for the community which will be held in June 2022 in the Purwobinangun Village. This activity was attended by 26 participants (mothers, teenagers, cadres, PKK, and others). The method used in health education is a contextual learning approach. Interactive methods with participants are also carried out and assisted with learning media such as LCD, PPT, and pointers. The results of the service show that there is an increase in public knowledge about stunting which includes understanding, causes, consequences, and efforts to prevent it as evidenced by an increase in the average score. The statistical test results also show that the significance value is 0.00. This means that there is an influence between the provision of health education about stunting on increasing the participants' knowledge, in this case mothers and adolescents. The recommendation from this activity is the need for continuous health promotion efforts by involving the community as program implementers. Activate existing activities in the community as a means of education. The use of appropriate health promotion media is also the key to public interest which in turn can increase public awareness of the information received.